Examining the Radiation-induced Bystander Effect (RIBE) and its Effect on Metabolism and Inflammation in Gastrointestinal Cancers - Heeran, Aisling (Trinity College Dublin. School of Medicine. Discipline of Surgery, 2021)
Radiation therapy is a mainstay of treatment for cancer. However, resistance to therapy remains a major clinical problem in rectal and oesophageal cancer, with at best only 27-30% of patients achieving a complete pathological response which is associated with enhanced patient outcomes. The mechanisms underlying treatment resistance are poorly understood. The radiation-induced bystander effect (RIBE) describes the plethora of biological events occurring in unirradiated cells adjacent to irradiated cells. RIBE has been linked experimentally to numerous hallmarks of cancer however, the examination of RIBE induction using human ex vivo models remains largely unknown in the literature. We investigated the effect of in vitro RIBE induction on mitochondrial metabolism and function and radiosensitivity in an in vitro model of colorectal cancer (CRC) and oesophageal adenocarcinoma (OAC), using a radiosensitive and a radioresistant cell line of both models. In vitro we did not observe any significant alterations in any of the parameters measured following RIBE induction using a single fraction of a clinically relevant dose of 1.8 Gy radiation in CRC cell lines. However, following RIBE induction using repeated fractions of 1.8 Gy radiation we identified a differential response in the radioresistant and radiosensitive OAC cell lines. Moreover, following RIBE induction using repeated fractions of 1.8 Gy radiation, we observed alterations in mitochondrial metabolism and function in both the radiosensitive and radioresistant cell line, as well as alterations in DNA repair in the radioresistant cell line. Since in vitro RIBE induction in the CRC model did not produce robust RIBE responses, we then investigated the effect of RIBE induction using a human ex vivo explant model of normal rectal tissue and rectal cancer tissue. RIBE induction ex vivo produced alterations in bystander cellular metabolism, with reductions in oxidative phosphorylation (OXPHOS) in bystander cells that were exposed to conditioned media (CM) from both irradiated normal and cancer tissue. Glycolysis was significantly reduced in bystander cells exposed to CM from irradiated rectal cancer tissue. RIBE induction did not alter mitochondrial function, however, elevated levels of reactive oxygen species (ROS) were observed in bystander cells treated with CM from rectal cancer tissue compared to normal rectal tissue. To gain a further understanding of the metabolites that may be driving these alterations, we examined the metabolomic landscape of normal rectal tissue and rectal cancer tissue pre- and post-radiation using 1HNMR. Leucine levels were significantly reduced in the CM of irradiated rectal cancer tissue compared to irradiated normal rectal tissue. Since obese rectal cancer patients have been reported to have poorer clinical outcomes, we correlated our biological end-point results with parameters of body composition and found significant correlations between visceral fat area (VFA) and leucine and ethanol in the rectal cancer secretome and levels of glycolysis and ATP production in bystander cells treated with the CM from the irradiated rectal cancer tissue. Since metabolism and inflammation are highly dependent and interconnecting processes, we next investigated the inflammatory landscape of ex vivo normal rectal tissue and rectal cancer tissue both pre- and post-radiation. We have shown that the rectal cancer microenvironment is more inflammatory than the normal rectal microenvironment, with elevated levels of 19 inflammatory proteins in the rectal cancer microenvironment; Flt-1, P1GF, CCL20, IFN-gamma, IL-10, IL-6, GM-CSF, IL-12/IL-23p40, IL-17A, IL-1alpha, IL-17A/F, IL-1RA, TSLP, CCL26, CXCL10, CCL22, CCL3, CCL4 and CCL17. Following radiation, IL-15 and CCL22 were elevated in the microenvironment of normal rectal tissue while no factor was significantly altered in the rectal cancer microenvironment. The irradiated rectal cancer microenvironment was the most potent inducer of dendritic cell maturation, suggesting that radiation does not negatively impact the ability of the rectal cancer microenvironment to mount an anti-tumour immune response. We also found significant correlations between body composition parameters and secreted factors, including correlations between VFA and CCL20 and inverse correlations between skeletal muscle and angiogenic markers including Flt-1 and VEGF-D. Having observed correlations between measures of obesity and response of bystander cells to radiation, levels of metabolites in the tumour microenvironment (TME) and altered levels of inflammatory proteins in the TME of obese individuals we profiled for the first time the metabolic signatures of ex vivo adipose tissue using Seahorse technology. We demonstrated that it was possible to determine the metabolic profiles of ex vivo adipose tissue depots using Seahorse technology and that OXPHOS predominates in visceral adipose tissue while there is a trend towards higher utilisation of glycolysis in subcutaneous adipose tissue. We then profiled the inflammatory protein secretions from both adipose tissue depots and found that there were significantly higher levels of angiogenic, vascular injury and proinflammatory secretions in the visceral compared to subcutaneous adipose tissue. There were also early indications in this preliminary study that obesity may alter the metabolic profile and inflammatory secretome of adipose tissue. Overall, the findings of this thesis have identified the interesting interplay of secreted factors and cell types within the TME as possible important determinants in regulating bystander cellular metabolism and innate immune responses in rectal cancer. We have also identified alterations in cellular behaviour, the metabolomic landscape and inflammatory protein secretions in obese patients compared to their non-obese counterparts. We have shown that Seahorse technology is a useful tool for profiling the metabolic signature of adipose tissue for future functional studies to more closely examine the interplay between obesity and RIBE and treatment responses in GI patients.
APPROVED
Keywords: Metabolism; Radiation-induced bystander effect (RIBE); Inflammation; Rectal cancer; Oesophageal cancer